Tahapan Pemeriksaan dan Pengajuan Upaya Hukum Dalam Pelaksanaan Putusan Hakim Untuk Perkara Pidana Secara Umum - Safari, Safari; Muhammad Aldi; Iskandar Riski; Fathullah, Fathullah (KRAKATAU (Indonesian of Multidisciplinary Journals), 2023)
In a crime problem, there will be many processes that will be faced by both law enforcement and the parties involved in the crime, one of the processes that really requires a very large level of energy is the inspection process. In this examination process there will be many stages that must be passed from examining case files, examining witnesses, expert witnesses, defendants to supporting documents as evidence of the crime which will eventually end in a judge's decision and how legal remedies are taken by the parties. -the parties involved where in this legal effort there will be many stages that will be passed to get justice from the start of appeal, cassation, clemency to the last is review and ends with the implementation of the judge's decision which has been determined whether the original decision or the decision after filing a legal remedy the. This study uses a research method with descriptive analysis by conducting data analysis by conducting interviews with related parties. The purpose of this research is for readers to understand more about the stages of examining criminal cases and how to deal with them.